(untitled) (Archives of Clinical Psychiatry, 2010)
OBJECTIVES: To review articles regarding important topics about cholinergic system and its ionotropic and G-protein coupled receptors as well as their regulation, also enlightening its importance in central nervous system (CNS) development and in several neuropsychiatric conditions such as Alzheimer disease, schizophrenia, epilepsy and smoking. METHOD: Bibliographical research was completed through MedLine, LILACS, PubMed, ISI and the Fundação Oswaldo Cruz Library, RJ, specifically for 1914 to 2009, using the descritors: "receptors", "cholinergic", Alzheimer "disease", "schizophrenia", "epilepsy" and "smoking", in addition to the cross-reference of the articles selected and further analyses of bibliographical references on the theme. RESULTS: Currently literature describes important effects of nicotinic and muscarinic receptors activation on development of central nervous system (CNS). The protein G coupled receptors dessensibilization and internalization mediated by kinases have been described in proliferation, differentiation and cell death, and also in neurologic disorders. DISCUSSION: The importance of the cholinergic system and its relationship with pathologies such as Alzheimer disease, schizophrenia, epilepsy is evident. The data produced so far may help on planning medicaments more specific for these pathologies treatment.